Conceptual foundations of technology and technological teaching: concepts, conceptions, and teaching performance (Research, Society and Development, 2022)
The phenomena of technology and technological education have been constituted in recent years as a space for broad debate. However, the deficiency in approaching the conceptual foundations of these phenomena in educational environments and the training of professionals is notorious. The research met this demand. It sought to bring provocations on the conceptual foundations of technology and technological education. Authors such as Reydon, Neder, Bazzo, Saviani, and Vygotsky, among others who contributed to the definitions and conceptions on this topic, were called to the debate. The research goal was to reveal the conceptual foundations of technology and technological education phenomena. It could contribute to an adequate understanding of technology and technological education and, finally, the importance of this relationship for teaching. It was possible to establish a concept of its own for each of the phenomena to contribute to the academic world and future works. An alternative means a good understanding of the terms above. The methodology used was the scientific-technological one, which established the identification of the problem, the guiding question, the organization of data, the answers, and the proposition of alternatives. The work managed to reveal a basis for the conceptual foundations of the phenomena. It enabled an accurate understanding of technology and technology education. The research concluded that the two phenomena investigated are themes present in educational environments, but they need to be understood more carefully for a practical awareness of the existing reality.